Síntese de trifluormetil-cicloalca[d]-2(1h)-pirimidinonas e tiopirimidinonas - Costa, Michelle Budke (2004)
This work describes the synthesis and identification of a serie of 4-trifluoromethylcycloalca[d]-2-(1H)-(thio)pyrimidinones, from the cyclocondensation reactions of 2-trifluoroacetylmethoxycycloalkenes with urea and thiurea. The 2-trifluoroacetylmethoxycycloalkenes were obtained from trifluoroacetylation of acetals derived from cycloalkanones. From this procedure, eight 2-trifluoroacetylmethoxycycloalkenes were obtained in good yields (60-70%), being that five are unpublished in literature. The cyclocondensation reaction using 2-trifluoroacetylmethoxycycloalkenes and urea or thiurea an carried out in alcoholic half under reflux, for 20 hours, catalysed by BF3.OEt2, leading to the products in 10-65% yields. The structural analyses of 2-trifluoroacetylmethoxycycloalkenes and 4- trifluoromethyl-cycloalca[d]-2-(1H)-(thio)pyrimidinones obtained were characterized by NMR 1H, 13C, CG/MS and elemental analysis. Still, were preliminary studies of NMR 17O for the 2-trifluoroacetylmethoxycycloalkenes.